Oocyte Maturation and miRNAs: Studying a Complicate Interaction to Reveal Possible Biomarkers for Female Infertility - Eleni Nazou; Anastasios Potiris; Despoina Mavrogianni; Eirini Drakaki; Aris-Anargyros Vogiatzis; Vaia Sarli; Tereza Vrantza; Athanasios Zikopoulos; Konstantinos Louis; Chara Skentou; Periklis Panagopoulos; Peter Drakakis; et al. (Diseases, 2024)
Cellular metabolism, apoptosis, fertilization, and proliferation of granulosa cells belong to a battery of processes where microRNAs can be detected and associated with infertility. The aim of the present review is to focus on mammalian oocyte maturation events and the association between oocyte growth and miRNA expression. PubMed/Medline, Google Scholar and Scopus databases were searched, and 33 studies were included. Regarding the correlation among miRNA expression and the regulation of granulosa cells and cumulus cells, the most important miRNAs were let-7b, let-7c and miR-21. Additionally, the loss of Dicer, an enzyme involved in miRNA biogenesis, is probably a crucial factor in oogenesis, oocyte maturation and embryogenesis. Furthermore, miRNAs interfere with different cellular mechanisms like apoptosis, steroidogenesis, genome integrity, angiogenesis, antioxidative response and, consequently, oocyte maturation. Hence, it is of major importance to clarify the role and mechanism of each miRNA as understanding its action may develop new tools and establish new diagnostic and treatment approaches for infertility and ovarian disorders.